Financial Development and Economic Growth: Evidence from Ten New EU Members - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Institute for the Study of Labor (IZA), 2014)
This paper reviews the main features of the banking and financial sector in ten new EU members, and then examines the relationship between financial development and economic growth in these countries by estimating a dynamic panel model over the period 1994-2007. The evidence suggests that the stock and credit markets are still underdeveloped in these economies, and that their contribution to economic growth is limited owing to a lack of financial depth. By contrast, a more efficient banking sector is found to have accelerated growth.
Keywords: E44; E58; F36; P26; 330; financial development; economic growth; transition economies